Landslide Hazard and Environment Risk Assessment - Miccadei, Enrico; Carabella, Cristiano; Paglia, Giorgio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Landslides are among the most widespread and frequent natural hazards. Landsliding is linked to the combination of geological, geomorphological, and climatic factors in response to trigger mechanisms, mostly represented by heavy rainfall events, seismicity, or human action. Landslides directly and indirectly impact a territory, causing fatalities and huge socio-economic losses. Consequently, to avoid serious consequences and support sustainable territorial planning, there is a clear need of correct land use policies and best practices for long-term risk mitigation and reduction. In this context, geomorphological field activities, satellite remote sensing, landslide susceptibility mapping, and innovative GIS analysis offer effective support for mapping and monitoring landslides' activity at both the local and regional scales. All landslide types are considered, from rockfalls to debris flows, from slow-moving slides to very rapid rock avalanches. Contributions to this Special Issue report key advances in landslide susceptibility mapping, environmental risk management in mass movement-prone areas, and landslide analysis in different geomorphological/morphostructural environments. Each article describes a distinct methodological approach to accurately investigate landslide phenomena and assess slope stability. Each article provides a scientific basis useful for the implementation of land planning, civil protection activities, and mitigation measures in different geological-geomorphological frameworks.